MENINJAU ULANG SNI 03 1733 2004 TENTANG SARANA PENDIDIKAN STUDI KASUS RADIUS PENCAPAIAN SARANA PENDIDIKAN DI KOTA MALANG - Rizal Brilliant Nugraha; Nuryantiningsih Pusporini; Fanita Cahyaning Arie; Firman Afrianto (UNHI PRESS, 2023)
An even distribution of educational facilities is necessary to equalize educational opportunities in a region. This research aims to evaluate the distribution of educational facilities based on the Indonesian National Standard (SNI) 03 1733 2004 in relation to the existing conditions, to ensure equal opportunities for education in Malang. The analysis methods used are hub line and hub distance analysis based on the points of residential areas and educational facility data from Google POI. The analysis results indicate that educational facilities in Malang have met, and even exceeded, the minimum standard radius of coverage for all educational units except for kindergartens. Therefore, educational facilities in the city of Malang are evenly distributed. This research can contribute to a better understanding of the spatial conditions of educational facilities and their coverage radius from residential areas. Furthermore, this research opens up opportunities for policymakers to evaluate the standards for providing educational facilities in large cities due to the increasing density of residential units, which results in shorter travel distances.